Development of a web-extension for authentication of online hadith texts - Kabir, M. Nomani; Hasan, Md Munirul; Rahman, Md. Arafatur; Tao, Hai (Science Publishing Corporation, 2018)
Background and objective: With the widespread internet availability, now-a-days Hadith texts which are essential sources of Islamic knowledge appear on many websites. In this paper, a client-based web-extension program that can authenticate online Hadith texts from Sahih Bukhari and Sahih Muslim is presented. Materials and Methods: First, the program reads the content of the specific browsed website and identifies Arabic language only. Then this Arabic text is screened to verify whether this contains any Hadith text by comparing with the authentic source. If complete match occurs in comparison, then the text is marked with green color proving the text as authentic. If some words/letters are missing, then the text will be marked with red color indicating that the Hadith is unauthentic and requires to be verified. Results: Using this web-extension, the authenticity of Hadith from Sahih Bukhari and Sahih Muslim can be verified simply by clicking a button of the web-extension. If the Hadith is unauthentic, it will display the authentic version of Hadith just by moving the mouse over the unauthentic text. Conclusion: This application will create Islamic consciousness for ordinary people. The application will also bene-fit government agencies of Islamic affairs, Hadith printing centers, etc.